Risk Factors Analysis in Patients with Knee Osteoarthritis at Al-Fauzan General Hospital: A Case Report - Makkiyah, Feda Anisah; Rahayu, Melinda Dwi; Supartono, Basuki; Heristyorini, Ayodya (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
One of the degenerative conditions frequently occurring in joints is Osteoarthritis (OA). OA is a common form of joint inflammation, the most prevalent one. Individual factors such as age, gender, body mass indices, occupation, family history, injury history, and body posture can increase the risk of knee OA. Knee OA is distinguished based on etiology, namely primary and secondary. Primary knee OA is often associated with genetic factors and natural aging, while secondary knee OA is caused by injuries, structural abnormalities, or other medical conditions. The purpose is to determine the relationship between risk factors in patients with knee OA. This research employed a cross-sectional design involving 56 patients selected through a total sampling technique at Al-Fauzan Hospital. The findings of the study reveal a significant association between the onset of OA and both age (p=0.000) and body posture (p=0.000). Nevertheless, factors such as gender (p=0.535), body mass indices (p=0.705), occupation (p=0.942), family history (p=0.321), and injury history (p=1.000) exhibit no correlation with knee OA. Age emerges as the most impactful factor linked to the occurrence of OA (OR=51.358). A notable correlation exists between age and body posture as risk factors for knee OA in patients. The probability of developing OA increases by a factor of 51.358 as individuals grow older compared to their younger counterparts.